A study on the effects of emotional expression training in music education on enhancing children’s psychological motivation - Jianyun Wei (Environment and Social Psychology, 2026)
The present article investigated the effects of emotional expressive training on music education on the psychological motivation among children based on quasi-experimental data provided by Guri music education project in Brazil. The results found that this training was significant in reducing the emotional symptoms in children and that the effect was more pronounced in children in families with low maternal educational level. The training also assisted children in acquiring a better understanding of musical selections and relate to the music emotionally, especially sad music. The study also indicates using the Self-Determination Theory that emotional promotion was a key element in internalizing the learning motivation, whereby, high-quality autonomous motivation was realized by satisfying the children with the need to belong and to be competent. This study presents a theoretical model, which correlates emotional enhancement to motivation internalization and recommends to employ systematic practice of emotional expression, in an autonomous-supportive instructional framework. The results present useful insights that would help in bettering the psychological and social development of children and give empirical evidence on why music education should be used as a means of promoting educational equity